Clinical manifestations of human immunodeficiency virus-induced uveitis - Paradee Kunavisarut (2018)
Purpose: To describe the clinical manifestations of patients with human immunodeficiency virus (HIV)-induced uveitis in Thailand. Design: Prospective cohort study of 6 patients with HIV-induced uveitis. Participants: Six patients (8 eyes) with HIV-induced uveitis who had an extremely high intraocular: plasma HIV-1 RNA ratio. Methods: The clinical manifestations and laboratory findings are reported of 6 consecutive patients with HIV-induced uveitis who had an extremely high intraocular-to-plasma HIV-1 RNA ratio and were diagnosed between July 2009 and May 2011. Main Outcome Measures: Clinical manifestations and laboratory findings. Results: Human immunodeficiency virus-induced uveitis was diagnosed in 4 men and 2 women with an average age of 41 years at presentation. None of the patients were receiving highly active anti-retroviral therapy (HAART) or had clinical or laboratory evidence, or both, of opportunistic infections. The mean plasma load was 218 688 copies/ml (median, 137 500 copies/ml; range, 24 900-540 000 copies/ml), and the mean intraocular HIV load was 20 937 755 copies/ml (median, 7 499 000 copies/ml; range, 2 460 000-89 800 000 copies/ml). The average CD4 cell count was 192 cells/μl (median, 248 cells/μl; range, 5-342 cells/μl). All the patients had decreased vision, and none had conjunctival hyperemia. The anatomic location of uveitis was anterior in all patients, and associated vitreitis was present in 4 patients; none exhibited retinal lesions or scars. Anterior segment inflammation and keratic precipitates were observed in all patients, and none responded to topical corticosteroid therapy. After the administration of HAART, the intraocular inflammation disappeared entirely within several weeks in all of the patients and the intraocular and plasma HIV loads decreased. Conclusions: Human immunodeficiency virus-induced uveitis should be suspected in HAART-naïve, HIV-positive patients or in those in whom this treatment fails and who have anterior uveitis without any retinal lesions and exhibit no response to topical corticosteroids. The concurrent determination of HIV load in the intraocular fluids and plasma may clarify the cause of HIV-associated uveitis. Financial Disclosure(s): The author(s) have no proprietary or commercial interest in any materials discussed in this article. © 2012 American Academy of Ophthalmology.